Factors that influence the enzymatic hydrolysis of agricultural wastes for ethanol production: a review - Natasha Kevellyn dos Santos; Daniel Pasquini; Milla Alves Baffi (The Journal of Engineering and Exact Sciences)
Lignocellulosic biomass, such as agricultural and forestry residues, can be reused and serve as sources of sugars for the production of second-generation ethanol (2G) and other bioproducts. However, these wastes are composed by molecules of difficult degradation, which require steps of pretreatment and enzymatic hydrolysis for their bioconversion into fermentable sugars. At the same time, chemical substances with a potential inhibitory effect on the microbial metabolism can also be produced after the pretreatments and hinder the overall yield of the hydrolytic process. For an efficient and low-cost hydrolysis, homemade enzymes produced from agroindustrial residues, such as sugarcane bagasse, can be employed. However, a set of parameters might be adjusted, such as: kind of pretreatment, enzyme load, solids load, hydrolysis time and use of additives, to improve the yields in free sugars using these onsite enzymatic preparations. In this sense, studies involving the optimization of the conditions of pretreatment and saccharification are essential to increase the bioconversion rate of lignocellulose. These strategies are important for the production of value-added products from these wastes and, consequently, offer a correct and profitable destination to them. Hence, this study presents a review of the main features that influence the enzymatic hydrolysis of agricultural wastes and the yield in reducing sugars for ethanol production.